Cognate frequency and assessment of second language lexical knowledge. (October 2019) - Allen, David
Aims and objectives/purpose/research questions: Few studies have investigated different-script cognate effects in language assessment contexts. This paper examines the impact of Japanese cognates in a test of English receptive lexical knowledge that is widely used for placement purposes in second language learning contexts. Specifically, the present paper utilizes Japanese cognate frequency to predict test accuracy. 1. Does Japanese cognate frequency influence response accuracy? 2. Does the effect vary by English word frequency and/or lexical proficiency? Design/methodology/approach: Seventy Japanese-English bilinguals completed the multiple-choice English VLT. Data and analysis: Accuracy data for 150 target items and 150 distractor items were analysed separately (10, 500 data points in each analysis). Generalized linear mixed-effects models were used with Japanese cognate frequency as the primary predictor and English word frequency and lexical proficiency as covariates. Findings/conclusions: A strong facilitatory cognate frequency effect was observed on both the selection of targets and the rejection of distractor items. This effect was marginally greater for lower proficiency learners. The English word frequency effect was also greater for lower proficiency test takers in the distractor analysis. Originality: The paper is the first to utilize cognate frequency to estimate the cognate effect in different-script languages in language testing. Significance/implications: The study provides robust evidence for the Japanese-English cognate effect in a test of lexical knowledge. This finding is broadly in line with the predictions of the bilingual interactive activation plus model of bilingual lexical processing. In addition, the paper demonstrates that the proportion of Japanese cognates in the test is significantly greater than the proportion of cognates in the language in general, indicating that it may over-estimate Japanese learners' knowledge of English lexis. Test designers and users are thus recommended to be aware of the impact of cognates when making inferences about language ability based on such tests of lexical knowledge.